54.6=6(m+2.9)

Simple and best practice solution for 54.6=6(m+2.9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 54.6=6(m+2.9) equation:


Simplifying
54.6 = 6(m + 2.9)

Reorder the terms:
54.6 = 6(2.9 + m)
54.6 = (2.9 * 6 + m * 6)
54.6 = (17.4 + 6m)

Solving
54.6 = 17.4 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
54.6 + -6m = 17.4 + 6m + -6m

Combine like terms: 6m + -6m = 0
54.6 + -6m = 17.4 + 0
54.6 + -6m = 17.4

Add '-54.6' to each side of the equation.
54.6 + -54.6 + -6m = 17.4 + -54.6

Combine like terms: 54.6 + -54.6 = 0.0
0.0 + -6m = 17.4 + -54.6
-6m = 17.4 + -54.6

Combine like terms: 17.4 + -54.6 = -37.2
-6m = -37.2

Divide each side by '-6'.
m = 6.2

Simplifying
m = 6.2

See similar equations:

| P=2(pi)*r+2x | | 36y+x=90 | | 400=2x+6x+4x | | 4x-27=3x | | 400=2x+6y+4z | | 4[3+c]=c+4 | | 90t=100+70t | | Y=.25x-2 | | 5-2k=27 | | -8n+4(1+5n)=-6n-1 | | 5h+2c+3h+5h+2c+3h= | | -6.8(x-1.25)=13.6 | | 4n^2+24n=0 | | 6x^4+4x^3+12x^2+4x-2=0 | | 54.9=6(m+2.9) | | 3x-75=27 | | 3n-0.03=(-9) | | 4x-5+2x+5=180 | | 0.6=54x | | Y+6y+y+2c+3c+2y+3c+2c= | | 3a+6y-89b= | | 2(r+9)=29 | | 2x+35-14x=26x+35 | | 7x+3=7(x-4) | | 0.31+0.15(x-1)+2.12=2.73 | | 8x^7-40x^5=0 | | 4h-10=2h-4 | | 5g+2(-3+3g)=1-g | | 4(6x-30)=72 | | f(5+5)=f(5)+f(5) | | 10y=7y+21 | | x^2+y^2=90 |

Equations solver categories